2021
DOI: 10.1021/acs.jproteome.0c00926
|View full text |Cite
|
Sign up to set email alerts
|

MegaGO: A Fast Yet Powerful Approach to Assess Functional Gene Ontology Similarity across Meta-Omics Data Sets

Abstract: The study of microbiomes has gained in importance over the past few years, and has led to the fields of metagenomics, metatranscriptomics and metaproteomics. While initially focused on the study of biodiversity within these communities the emphasis has increasingly shifted to the study of (changes in) the complete set of functions available in these communities. A key tool to study this functional complement of a microbiome is Gene Ontology (GO) term analysis. However, comparing large sets of GO terms is not a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…We observed that the functional similarity between data sets acquired with different workflows on each sample is extremely high, and this regardless of the approach chosen. For the peptide-centric approach, we compared the Gene Ontology (GO) terms (GO domain “biological process”) provided by Unipept for each of the identified peptides with MegaGO 64 , resulting in MegaGO similarities of 0.96 or higher. Notably, 95% of the identified peptides were associated with at least one GO term.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the functional similarity between data sets acquired with different workflows on each sample is extremely high, and this regardless of the approach chosen. For the peptide-centric approach, we compared the Gene Ontology (GO) terms (GO domain “biological process”) provided by Unipept for each of the identified peptides with MegaGO 64 , resulting in MegaGO similarities of 0.96 or higher. Notably, 95% of the identified peptides were associated with at least one GO term.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, there appears to be an important contribution to any observed differences from the sequence database used for identification. This is particularly evident in the protein inference step, where peptide-level degeneracy in the database becomes an important factor in the outcome of protein grouping, as already shown and discussed previously 63,64 . Overall, functional profiles of different proteomics workflows were quite similar, which is a reassuring characteristic due to the unique perspective provided by proteomics on the functional level.…”
Section: Discussionmentioning
confidence: 72%
“…Knowledge of relations between toxicity pathways may also inform the ranking and/or severity weighting. As a step in this direction, it was illustrated how derivation of the genomic RPP could be supported by approaches for assessing semantic similarities between GO terms using the web application by Verschaffelt et al (2021) as an example. Interestingly, the similarity score across the genomic RPP was dose dependent (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of GO categories using tools for computation of similarity scores may potentially help to refine the determination of Sijk values as well as supporting parameterization of the systemic weight function, w(S), in equation (3). To illustrate this potential the web application (MegaGO) from Verschaffelt et al, (2021) was used that calculates similarity between GO terms with the relevance semantic similarity metric (Lin, 1998). The tool provides a score between 0 and 1 for each of the three GO domains, but for the present data a score for "biological process" results exclusively since this is the only domain covered.…”
Section: Refinement Of S-values and Severity Weightingmentioning
confidence: 99%
See 1 more Smart Citation